Spontaneous Chest Wall Hematoma - Unusual Presentation of Chronic Myeloid Leukemia - George, Peter; Duble, Shishir Nagesh; Hegde, Narasimha (Journal of Medicine, 2012)
Chronic Myeloid Leukemia (CML) is known for the variety of its clinical presentations. We report on a 45 year old male, who presented with sudden swelling over chest wall on lifting weight; and clinically with pallor and massive splenomegaly. The peripheral, bone marrow smears; and chromosomal study confirmed CML. In this report, we have depicted interesting clinical, sonographic and microscopic images. To our knowledge, this is possibly the first report on CML presenting as spontaneous chest wall hematoma. DOI: http://dx.doi.org/10.3329/jom.v13i1.10082 JOM 2012; 13(1): 94-96